(untitled) (International Journal of Engineering and Computer Science, 2013)
Biofuel is as old as the existence of man, made of three categories; solid, liquid and gas. Dried manure, charcoal and wood are well known solid biofuels .The liquid biofuels include; biodiesel, bioethanol, biobuthanol and biopropanol. The last three are called bioalcohols of which, biopropanol is the least commonly use in this group and biothenol the most. Biogases are methane and Syngas. Biodiesel can be produced by homogenous and heterogeneous catalysis with heterogeneous catalysis now found to be better process. The liquid biofuels burn better than fossil fuels and therefore give engines longer lives. Bioethanol has higher octane rating than gasoline. Both biodiesel and bioethanol mix completely with conventional diesel and gasoline respectively. This review highlights the benefits of biofuels and their production.